Imaginary on International Migrants’ Human Rights in the Legal System: Some Limitations to the Principle of Universality in the Case of Argentina - González, Anahí Patricia (2017)
The purpose of this study is to analyze social representations of members of the legal system about human rights of international immigrants arrived to Argentina in the second half of 20th century. A qualitative methodological strategy was implemented; semistructured interviews to members of the legal institution of Buenos Aires metropolitan area were used. The interviews were transcribed and processed with qualitative criteria by implementing the Strauss and Corbin's (2002) methodology. This article analyses two relevant dimensions: citizens’ rights and migration policies. Among the main findings in the discourse of the subjects interviewed, it can be said that negative social representations about foreign people and their arrival to the country prevail. Even though there is a gradient of opinions whose extremes meet. On the one hand, there are those affirming equality (formal) in the access to all rights for native and migrant population. On the other hand, there are those who propose the priority of access to these rights for native subjects. The principle of universality from a human rights perspective is dwarfed when compared to the position of those who consider the migration control, the restriction of the arrival of migrants, and the closure of national borders as essential